An Analysis of Lexical Cohesion in Donald Trump's Speech to the UN General Assembly 2017 - Isma Farikha Latifatun Nuzulia; Istiqomah Wulandari (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2020)
The aim of this research is to define a linguistic framework based on Donald Trump's manuscript at the 2017 General Assembly since Trump is an influential person in the world and it was essential to note how the impact of his speech could have a strong effect on audiences. This research uses a descriptive qualitative approach to analyze and describe the types of lexical cohesion of HallidayHasan (1976) and Renkema's Theory (2004). In regard, the researchers analyze the most frequently known types of lexical cohesion following the analysis of the data and drawing conclusions based on the results. The findings showed that 80 data were found and 36 data included repetitions, 10 synonyms, 2 general terms, 3 superordinates, 10 collocations, 5 hyponymies, 6 antonyms, 27 anaphoras, and no cataphora and metonymy found in this analysis. After analyzing the results, the most dominant type found was repetition, which meant emphasizing their speech to show how powerful the American and show profound admiration for others.